2022
DOI: 10.1039/d2nr02399g
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature formation of alloy ZnxCd13−xSe13 magic-size clusters via cation exchange in diamine solution

Abstract: Magic-size clusters (MSCs) are molecular-like materials with unique properties at the border between molecules and solids, providing important insights into the nanocrystal formation process. However, the synthesis of multicomponent alloy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…However, the development of CE reactions provides a feasible approach to overcome this challenge. Based on this strategy, binary, ternary and even quaternary alloyed nanocrystals have been realized [18,106,[115][116][117][118]. As exhibited in Fig.…”
Section: Synthesis Of 0d Tmc Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the development of CE reactions provides a feasible approach to overcome this challenge. Based on this strategy, binary, ternary and even quaternary alloyed nanocrystals have been realized [18,106,[115][116][117][118]. As exhibited in Fig.…”
Section: Synthesis Of 0d Tmc Alloysmentioning
confidence: 99%
“…Moreover, precise control over the In/Zn ratio was achieved, and it was observed that increasing the Zn content resulted in an observable blue shift [118]. Up to now, various 0D alloyed TMC materials have been realized by CE reactions, including Zn x Cd 13-x Se 13 magic-size clusters [117], AgInS 2 nanoparticles [119] and Au@Ag 2 ZnSnS 4 core-shell nanocrystals [120], etc. This synthesis strategy not only offers a protocol for the precise construction of 0D TMC nanocrystals with desired structures and composition, but also contributes to enhancing the structural complexity and diversity to TMC materials.…”
Section: Synthesis Of 0d Tmc Alloysmentioning
confidence: 99%
“…We used Cd(Ac) 2 /oleylamine (Cd(Ac) 2 /OLA) as a precursor for a partial cation exchange reaction with pre-synthesized ZnSe MSCs in diamine solution and determined the obtained ZnCdSe MSC molecular formula as Zn x Cd 13− x Se 13 MSCs ( x = 1–12) by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and X-ray photoelectron spectroscopy (XPS). 31 Unfortunately, the preparation of CdTe MSCs based on the cation exchange method has still not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The cation exchange method, which is often used for the synthesis and conversion of QDs, has also been applied to the synthesis of MSCs. [29][30][31][32] In 2016, the conversion of CdSe MSCs into Cu 2 Se MSCs was realized by White et al for the first time by cation exchange and the presence of cation exchange process intermediates was monitored using absorption spectra. 29 Stein et al employed cadmium phenylacetate as a Cd precursor for cation exchange with InP MSCs, and Cd-In-P alloy MSCs or CdP MSCs were obtained by modulating the amount of Cd incorporation.…”
Section: Introductionmentioning
confidence: 99%